2023
DOI: 10.1186/s12879-023-08669-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mouthwash on reducing salivary SARS-CoV-2 viral load and clinical symptoms: a systematic review and meta-analysis

Mingrui Zhang,
Nan Meng,
Hong Duo
et al.

Abstract: Background COVID-19 has been a public health emergency of international concern (PHEIC) for a lengthy period of time. The novel coronavirus is primarily spread via aerosols at a short distance, with infected individuals releasing large amounts of aerosols when speaking and coughing. However, there is an open question regarding whether mouthwash could effectively reduce virus transmission during the COVID-19 pandemic and support the prevention of infection among medical workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A recent randomized, double-blind, controlled clinical trial has also indicated that SARS-CoV-2 RNA copy numbers were stable for up to 60 min after the use of 0.05% CPC mouthwash [ 16 ]. Recent systematic reviews have also shown that using 0.075% CPC-containing mouthwashes may not be effective in reducing SARS-CoV-2 viral load [ 40 , 41 ]. This might be due to the fact that the antiviral effects of CPC against SARS-CoV-2 are the result of lipid membrane disruption in the viral envelope, without an effect on viral RNA integrity [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized, double-blind, controlled clinical trial has also indicated that SARS-CoV-2 RNA copy numbers were stable for up to 60 min after the use of 0.05% CPC mouthwash [ 16 ]. Recent systematic reviews have also shown that using 0.075% CPC-containing mouthwashes may not be effective in reducing SARS-CoV-2 viral load [ 40 , 41 ]. This might be due to the fact that the antiviral effects of CPC against SARS-CoV-2 are the result of lipid membrane disruption in the viral envelope, without an effect on viral RNA integrity [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis reported a positive impact of mouthwashes on SARS-CoV-2 Ct values compared with the control group, especially within 30 min of rinsing. However, none of the included studies explored the impact of CPC-CHX on SARS-CoV-2 viral load (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%